A structured taxonomy for effective digital transformation project implementation: Development, validation, and practical insights - Rahnuma Tarannum; Bertha Joseph Ngereja; Bassam Hussein (International Journal of Information Systems and Project Management)
The aim of this study was to develop and validate a taxonomy designed to assist organizations in formulating their Digital Transformation Project implementation strategies. In creating this taxonomy, we sought to blend both conceptual frameworks and empirical data. The initial phase involved a scoping review that synthesized existing literature to lay the foundation for the taxonomy. Subsequently, we aimed to validate the taxonomy by gathering feedback from industry experts in Germany using a closed card sorting technique, complemented by case study analysis. This structured compilation of information regarding implementation strategies, presented through the taxonomy, simplifies the process for practitioners. Such a taxonomy enables practitioners to adopt a standardized vocabulary, which supports decision-making, encourages learning from previous successes and challenges, and facilitates the application of these lessons to their projects. Additionally, we have included practical case scenarios within the taxonomy, offering guidance for organizations on leveraging it in the execution of digital transformation projects.